DINAMIKA PARTISIPASI REMAJA DALAM KEGIATAN KEAGAMAAN MASJID: STUDI KASUS IKATAN REMAJA MASJID RIYADUL JANNAH - Julia Lestary, Selvy; Oyoh Bariah; Afiyatun Kholifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the dynamics of youth participation in religious activities at Riyadul Jannah Mosque and to identify the factors influencing the sustainability of such activities. The research was motivated by the prolonged inactivity of the mosque youth organization, despite previous efforts to reactivate it. A qualitative case study approach was employed, with data collected through in-depth interviews with mosque youth members, mosque administrators, and community leaders, as well as observations and documentation. The findings indicate that youth participation in religious activities tends to be fluctuating and inconsistent. At certain periods, activities such as Islamic study sessions, commemorations of Islamic holy days, and socio-religious programs were conducted, yet they lacked continuity. Supporting factors included religious motivation and peer encouragement, while inhibiting factors consisted of work and educational commitments, weak organizational coordination, and limited structural support from mosque authorities. These conditions contributed to the difficulty in sustaining youth religious activities. The study highlights the importance of strengthening organizational management and institutional support to maintain the existence of mosque youth as an integral part of mosque-based religious activities.